Complexes in Relative Elliptic Theory - Izvarina, Natalia; Savin, Anton (Eurasian Mathematical Journal, 2020)
Given a pair (M,X), where X is a smooth submanifold in a smooth manifold M, we consider complexes of operators associated with this pair. We describe the notion of ellipticity in this situation and prove the Fredholm property for elliptic complexes. As applications, we consider the relative de Rham complex and Dolbeault complex.